Optimization of Agrobacterium– mediated transformation conditions for cotton (Experimental biology, 2015)
In this article are provided a data on optimization of Agrobacterium–mediated transformation conditions for cotton domestic varieties. The optimal concentration of acetosyringone (100 μM), the optical density of a suspension of bacterial cells (0,6) and co-cultivations time (48 hours) with A.tumefaciens strain LBA4404 for the Agrobacteriummediated transformation of cotton explants are revealed. The results will be used for creation of transgenic plants ofdomestic cotton varieties resistant to herbicide Basta.
Keywords: the cotton; the Agrobacterium-mediated transformation